Synthesis and Biological Evaluation of (−) and (+)‐Spiroleucettadine and Analogues. (26th January 2021) - Badart, Michael P.; Barnes, Emma M.; Cording, Andrew P.; Gilmer, Selena C. L.; Billinghurst, Ian D.; Edupuganti, Veera V. Shivaji R.; Lessene, Guillaume; Bland, Abigail R.; Bower, Rebekah L.; Rana, Zohaib; Ferguson, Scott A.; Opel Reading, Helen K.; et al.
Abstract: A second‐generation enantiospecific synthesis of spiroleucettadine is described. The original reported antibacterial activity was not observed when the experiment was repeated on the synthetic samples; however, significant anti‐proliferative activity was uncovered for both enantiomers of spiroleucettadine. Comparison of the optical rotational data and ORD‐CD spectra of both enantiomers and the reported spectrum from the natural source have not provided a definitive answer regarding the absolute stereochemistry of naturally occurring spiroleucettadine. Efforts then focussed on alteration at the C‐4 and C‐5 positions of the slightly more active (−)‐spiroleucettadine. Ten analogues were synthesised, with three analogues found to possess similar anti‐proliferative profiles to spiroleucettadine against the H522 lung cancer cell line. Abstract : The pluses and minuses of unexpected results : The second‐generation synthesis of spiroleucettadine is described along with its unexpected anti‐proliferative properties. This improved synthesis enabled access to large quantities of both enantiomers of spiroleucettadine and structural analogues. Three spiroleucettadine analogues were found to possess similar potency as spiroleucettadine against lung cancer cells.